Sistem Informasi Geografis Pemetaan Kawasan Permukiman Kumuh Kota Pontianak Berbasis Website - Dandi Suagira Buana; Renny Puspita Sari; Syahru Rahmayuda (Universitas Budi Darma, 2022)
The increase in population every year triggers various problems including the accumulation of population in one particular area which can potentially lead to new slum areas. Information regarding the distribution of slum settlements has not been published, so people do not know the area they will be increasing or including the slum area. In overcoming these problems, a Geographic Information System (GIS) was designed to digitally map the distribution of slum areas using calculations based on PUPR Ministerial Regulation No. 14 of 2018 concerning Prevention and Quality Improvement of Slum Housing and Slum Settlements. The determination was calculated using 7 indicators and 16 criteria and resulted in 3 classifications of slum level consisting of light slums, medium slums, and heavy slums. The final result of this research is expected to help the relevant government and the community in knowing the distribution area of slums based on WebGIS. Black-box testing is used to test the functionality of the system that was built and get good results with details of all functions running and following the design stage. Testing the system interface was carried out using an online questionnaire filled out by 38 respondents, resulting in a percentage of 87.5% calculated using a Likert scale so that it was categorized as excellent.